Transparansi Pelayanan Izin Mendirikan Bangunan (IMB) di Kantor Badan Pelayanan Perizinan Terpadu Kabupaten Mamuju - Rudi Rudi; Muhammad Yunus; Hasrat Arief Saleh (Universitas Muhammadiyah Gorontalo, 2018)
Transparency of the services provided by government agencies in administering public services is very important so customer can easily find out information or access about the procedure / stages in the services provided by her government agencies. The aim of the research is to describe, measure and analyse the transparency of building construction permit in Mamuju Regency. The research was a descriptive qualitative and quantitative (mix method) study. The methods of obtaining the data were questionnaire, interview and observation to informants who are directly involved in building construction permit. The results of the research indicate that the implementation process of service transparency of building construction permit in Mamuju Regency has not been fully implemented based on transparency dimensions expected by the customers/community. There are still some points that should be informed clearly and precisely to the costomers/community especially in terms of service implementation management, technical and administrative requirements, service completion time, authorized and responsible officials, service appointments, service location, and service standard. Meanwhile, the points that can meet the transparency dimensions are service procedure, service cost, and information of service consultation/complaint process that are sufficient to provide information that is clear, precise, and easy to understand. The lack of transparency of the points mentioned above is because the authorized and responsible officials do not have commitment in providing clear and precise information for the costomers/community, so a certainty in service is not created. Transparansi pelayanan sangat penting bagi instansi pemerintah dalam penyelenggaraan pelayanan publik, karena dengan adanya transparansi pelayanan terhadap masyarakat/pelanggan dapat dengan mudah mengetahui informasi atau akses tentang prosedur-prosedur dalam pelayanan yang diberikan olen instansi pemerintah. Penelitian ini bertujuan menggambarkan, mengukur, dan menganalisa transparansi pelayanan izin mendirikan bangunan (IMB) di Kabupaten Mamuju. Penelitian ini merupakan penelitian deskriptif kualitatif dan kuantitatif (mix method). Data dikumpulkan melalui kuesioner, wawancara, dan observasi terhadap informan yang terlibat langsung dalam pelayanan IMB. Hasil penelitian menunjukkan bahwa proses penerapan transparansi pelayanan IMB Kabupaten Mamuju belum sepenuhnya diterapkan dalam dimensi-dimensi transparansi yang diharapkan oleh masyarakat. Masih terdapat beberapa aspek yang harus diinformasikan secara jelas dan tepat kepada masyarakat terutama dari segi manajemen penyelenggaraan pelayanan, persyaratan teknis dan administrasi, waktu penyelesaian pelayanan, pejabat yang berwenang dan bertanggung jawab, janji pelayanan, lokasi pelayanan, dan standar pelayanan. Adapun aspek yang telah memenuhi dimensi-dimensi transparansi, yaitu prosedur pelayanan, biaya pelayanan dan informasi proses konsultasi/pengaduan pelayanan sudah memberikan informasi yang jelas, tepat, dan mudah dipahami.